2021
DOI: 10.3390/ma14051162
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Additive Manufacturing: Mechanical Response of Polyethylene Terephthalate Glycol over Multiple Recycling Processes

Abstract: The continuous demand for thermoplastic polymers in a great variety of applications, combined with an urgent need to minimize the quantity of waste for a balanced energy-from-waste strategy, has led to increasing scientific interest in developing new recycling processes for plastic products. Glycol-modified polyethylene terephthalate (PETG) is known to have some enhanced properties as compared to polyethylene terephthalate (PET) homopolymer; this has recently attracted the interest from the fused filament fabr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
43
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 36 publications
1
43
0
1
Order By: Relevance
“…During the second recycle course, Young’s modulus decreased by 25%, while tensile and fracture strength decreased by 10% at the third recycle course, causing a reduction in toughness by 37% [ 50 ]. Moreover, in the fourth recycle course, the impact strength and micro-hardness increased by 59% and 27%, respectively, and the tensile strength increased by 20% in the fifth recycle course [ 51 ]. This change in mechanical properties is due to multiple recycling, the slight change in polymer viscosity, inter-bead porosity, insufficient change in molecular weight or polydispersity index, and cross-linking during polymer waste processing [ 50 ].…”
Section: Reuse Of Waste Plastic In Fdmmentioning
confidence: 99%
See 2 more Smart Citations
“…During the second recycle course, Young’s modulus decreased by 25%, while tensile and fracture strength decreased by 10% at the third recycle course, causing a reduction in toughness by 37% [ 50 ]. Moreover, in the fourth recycle course, the impact strength and micro-hardness increased by 59% and 27%, respectively, and the tensile strength increased by 20% in the fifth recycle course [ 51 ]. This change in mechanical properties is due to multiple recycling, the slight change in polymer viscosity, inter-bead porosity, insufficient change in molecular weight or polydispersity index, and cross-linking during polymer waste processing [ 50 ].…”
Section: Reuse Of Waste Plastic In Fdmmentioning
confidence: 99%
“…The thermal test performed over the R-ABS parts revealed that the probability of random chain scission in processed material due to thermo-mechanical recycling results in a decrease in glass transition temperature ( T g) and a reduction in the material's mechanical properties [ 36 ]. In the fifth course of recycling, the T g increases, but after the fifth recycling course, chemical degradation occurs, leading to the breakage of the polymeric chain of the parts [ 51 ].
Fig.
…”
Section: Reuse Of Waste Plastic In Fdmmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 2 presents the flow chart of the current research. ABS was selected as it is the second-most popular material in MEX 3D printing [45]. For the preparation of the experiments' workpieces, industrial-grade Terluran Hi-10 ABS in powder form was procured from INEOS Styrolution (INEOS AG, Frankfurt, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Additively manufactured components are increasingly used as structural components in today's technical practise. [1][2][3] The time required to obtain a working component or assembly is drastically reduced using this method. Therefore, it is important to think about how different mechanical loads and the effects of the environment over time will affect the final part's qualities and behavior.…”
mentioning
confidence: 99%